Loss of Adipocyte STAT5 Confers Increased Depot-Specific Adiposity in Male and Female Mice That Is Not Associated With Altered Adipose Tissue Lipolysis - Richard, Allison J.; Hang, Hardy; Allerton, Timothy D.; Zhao, Peng; Mendoza, Tamra; Ghosh, Sujoy; Elks, Carrie M.; Stephens, Jacqueline M. (Frontiers in Endocrinology, 2022)
STATs (Signal Transducers and Activators of Transcription) 5A and 5B are induced during adipocyte differentiation and are primarily activated by growth hormone (GH) and prolactin in fat cells. Previous studies in mice lacking adipocyte GH receptor or STAT5 support their roles in lipolysis-mediated reduction of adipose tissue mass. Male and female mice harboring adipocyte-specific deletion of both STAT5 genes (STAT5AKO) exhibit increased subcutaneous or inguinal adipose tissue mass, but no changes in visceral or gonadal fat mass. Both depots display substantial increases in adipocyte size with no changes in lipolysis in adipose tissue explants. RNA sequencing analysis of subcutaneous adipose tissue and indirect calorimetry experiments reveal sex-dependent differences in adipocyte adipose gene expression and whole-body energy expenditure, respectively, resulting from the loss of adipocyte STAT5.